The relevance of the development of food products enriched with trace elements for diet therapy in cardiovascular diseases - A. N. Yashin; A. N. Petrov (Пищевые системы)
Cardiovascular diseases (CVDs) remain to be the leading cause of death in the whole world. The structure of nutrition of the population and diet therapy are extremely important factors for prevention and treatment of CVDs. Results of the scientific research obtained over the last decade give new data on the role of certain micronutrients in the physiological processes and pathogenesis of these groups of diseases. The aim of this research was to study the current role of certain trace elements (magnesium, zinc and copper) in the pathogenesis of diseases, including assessment of the level of their intake in different countries. Furthermore, the review considers the necessity of creating new functional products to use in diet therapy for patients with cardiovascular diseases. It includes publications in Russian and English for the period of 2011 to 2022 from open databases PubMed, ScienceDirect, Scopus, CyberLeninka, eLIBRARY as well as from open Internet sources. The research work carried out during preparation of this review was directed to studying the sphere of CVD prevention, role and relevance of the development of functional foods enriched with micronutrients. The data on the dysfunctions of the human body caused by the deficiency of zinc, copper and magnesium intake are presented. The current physiological daily norms for intake of these trace elements in different countries are given, and the dynamics of changes in the norms of intake over the last twenty years is shown. The review summarizes new data on the correlation between the risk of emergence of certain CVD types and the specific features of assimilation of the above-mentioned trace elements. The regulatory conditions acting on the RF territory for introducing trace elements into food products are analyzed. Based on the obtained results, conclusions were made regarding the relevance of the further development of functional foods that do not require changes in the traditional food behavior model.